Exogenous salicylic acid, abscisic acid, and shikimic acid enhance drought tolerance in tea by modulating antioxidant defense and osmotic regulation - Shelina Akter Sheuli; Mir Sultanul Arafin; Sadia Sultana; Md. Afser Rabbi; Ajit Ghosh (PLoS ONE, 2025)
Tea (Camellia sinensis), a widely cultivated crop across more than 50 countries, is highly vulnerable to drought stress, which impairs growth and reduces yield. This study examines the potential of exogenously applied salicylic acid (SA), abscisic acid (ABA), and shikimic acid (ShA) in enhancing drought tolerance in tea plants. Plants were pre-treated with SA, ABA, and ShA for 4 days, followed by 10 days of drought stress during which no water was provided by either foliar spray or soil irrigation. Leaf samples collected on day 15 were analyzed for various physiological and biochemical markers, including antioxidant enzyme activities (POD and GST), reactive oxygen species (H2O2) levels, and contents of total chlorophyll, carotenoids, and proline. Results showed that all treatments mitigated drought-induced physiological damage, reduced oxidative stress, and elevated antioxidant enzyme activity compared to untreated control plants under drought conditions. Treated plants also exhibited higher proline and chlorophyll levels, suggesting improved osmotic regulation and photosynthetic efficiency. Among the treatments, SA demonstrated the most pronounced enhancement of drought tolerance. To clarify the functional roles and relationships of 76 genes found through a literature review associated with the SA and ShA pathways under drought stress were examined using Gene Ontology (GO) enrichment, subcellular localization, and KEGG pathway analysis. These findings indicate that exogenous application of SA, ABA, and ShA enhances drought resilience in tea by strengthening antioxidant defenses and maintaining cellular integrity, presenting a promising approach to sustaining tea production in drought-prone areas. Future studies should explore the potential of combining these inducers with genetic or microbial strategies to further enhance drought resilience in tea plants.